Colloidal III–V Quantum Dot Photodiodes for Short‐Wave Infrared Photodetection. Issue 17 (10th April 2022) - Leemans, Jari; Pejović, Vladimir; Georgitzikis, Epimitheas; Minjauw, Matthias; Siddik, Abu Bakar; Deng, Yu‐Hao; Kuang, Yinghuan; Roelkens, Gunther; Detavernier, Christophe; Lieberman, Itai; Malinowski, Paweł E.; Cheyns, David; et al.
Abstract: Short‐wave infrared (SWIR) image sensors based on colloidal quantum dots (QDs) are characterized by low cost, small pixel pitch, and spectral tunability. Adoption of QD‐SWIR imagers is, however, hampered by a reliance on restricted elements such as Pb and Hg. Here, QD photodiodes, the central element of a QD image sensor, made from non‐restricted In(As, P) QDs that operate at wavelengths up to 1400 nm are demonstrated. Three different In(As, P) QD batches that are made using a scalable, one‐size‐one‐batch reaction and feature a band‐edge absorption at 1140, 1270, and 1400 nm are implemented. These QDs are post‐processed to obtain In(As, P) nanocolloids stabilized by short‐chain ligands, from which semiconducting films of n ‐In(As, P) are formed through spincoating. For all three sizes, sandwiching such films between p ‐NiO as the hole transport layer and Nb:TiO2 as the electron transport layer yields In(As, P) QD photodiodes that exhibit best internal quantum efficiencies at the QD band gap of 46±5% and are sensitive for SWIR light up to 1400 nm. Abstract : A complete process flow to form photodiode stacks sensitive for short‐wave infrared (SWIR) light based on non‐restricted In(As, P) quantum dots (QDs) is proposed. Films made of semiconducting n ‐In(As, P) QDs inks, formulated through apolar/polar QD phase transfer, form a rectifying junction with p ‐NiO that is photosensitive beyond 1400 nm. This result highlights the prospect of printable SWIR opto‐electronics based on InAs QDs.